Equity premium predictability over the business cycle - Mönch, Emanuel,Stein, Tobias (Deutsche Bundesbank, 2021)
The equity premium follows a pronounced v-shape pattern around the beginning of recessions. It sharply drops into negative territory just before business cycle peaks and then strongly recovers as the recession unfolds. Recessions are preceded by an inverted yield curve. Thus probit models using the term spread as predictor time the beginning of recessions well. We show that such model-implied recession probabilities strongly improve equity premium prediction out-of-sample. We document a structural break in the mean of the term spread in 1982. When correcting for this break, the forecast performance further strengthens, outperforming other recently proposed benchmark predictors.
urn:nbn:de:101:1-2021081310334172807624
Keywords: Graue Literatur; Recession predictability; return predictability; business cycle; probit model; term spread